Thoracic Aortic Aneurysm Growth: Role of Sex and Aneurysm Etiology - Cheung, Katie; Boodhwani, Munir; Chan, Kwan‐Leung; Beauchesne, Luc; Dick, Alexander; Coutinho, Thais (Journal of the American Heart Association, 2017)
Background Thoracic aortic aneurysm (TAA) outcomes are worse in women than men, although reasons for sex differences are unknown. Because faster TAA growth is a risk factor for acute aortic syndromes, we sought to determine the role of sex and aneurysm etiology on TAA growth. Methods and Results Eighty‐two consecutive unoperated subjects with TAA who had serial aneurysm measurements were recruited. In multivariable linear regression the association of female sex with aneurysm growth rate was assessed after adjustment for potential confounders. We also tested the interaction term sex×aneurysm etiology in the prediction of TAA growth. Seventy‐four percent of subjects were men; mean±SD age was 62.4±11.9 years in men and 67.7±10.7 years in women (P=0.06). Forty‐seven (57%) subjects had degenerative TAAs, and the remainder had heritable TAAs. Absolute baseline aneurysm size and follow‐up time were not different between men and women. Aneurysm growth rate was 1.19±1.15 mm/y in women and 0.59±0.66 mm/y in men (P=0.02). Female sex remained significantly associated with greater aneurysm growth in multivariable analyses (β±SE: 0.35±0.12, P=0.005). In addition, female sex was associated with faster TAA growth only among those with degenerative TAA (β±SE: 0.33±0.08, P=0.0002) and not among those with heritable TAA (P=0.79), with a significant sex×etiology interaction (P=0.001). Conclusions TAA growth rates are greater in women than men, and this difference is specific to women with degenerative TAAs. Our findings may explain sex differences in TAA outcomes and provide a foundation for future investigations of this topic.